The effect of the number of conveyor belt carrying idlers on the failure of an impact place: A failure analysis. (July 2017) - Honus, Stanislav; Bocko, Peter; Bouda, Tomáš; Ristović, Ivica; Vulić, Milivoj
Abstract: The article deals with the failure analysis of a conveyor belt related to the place of impact where material lands. It studies how the number of conveyor carrying idlers influences the belt compression stress in the place of impact. The landing material is represented by an impactor of 500 kg landing from the height of 4 m. The analyses are grounded in mathematical modelling of the transport belt and experimentally determine the quantities vital for the simulations. The place of impact under examination is the critical site of the whole facility as it is subject to extreme stress. The failure analysis considers two variants of idler number in the place of material impact. The results clearly demonstrate that the construction making use of a higher number of idlers is more suitable due to lower deformations of the belt. The conclusions presented in the article may thus lead to conveyor belt construction optimisations, and thus contribute to their longer life. At the same time, there is a great potential for further research, as the topic of longer conveyor belt life via changing the number of carrying idlers at the place of impact has not been widely investigated. Highlights: A failure analysis of a belt conveyor at the place of impact was carried out. Different numbers of carrying idlers were tested to observe their effect at this critical site. A higher number of idlers reduces the size of deformation energy carried by the belt. With a higher number of idlers the transport belt is subject to less strain due to material landing. Longer life of transport belts is ensured.